Racial and Ethnic Differences in Older Adults With Knee Osteoarthritis. Issue 7 (July 2014) - Cruz‐Almeida, Yenisel; Sibille, Kimberly T.; Goodin, Burel R.; Petrov, Megan E.; Bartley, Emily J.; Riley, Joseph L.; King, Christopher D.; Glover, Toni L.; Sotolongo, Adriana; Herbert, Matthew S.; Schmidt, Jessica K.; Fessler, Barri J.; et al.
<x xml:space="preserve">Abstract</x> Objective Knee osteoarthritis (OA) contributes significantly to disability in older individuals, and racial/ethnic minorities are disproportionately affected. The present study aimed to characterize differences in clinical and experimental pain, including pain inhibition, among older African American (AA) and non‐Hispanic white (NHW) subjects with knee OA. Methods AA and NHW subjects with knee OA (n = 267) completed clinical and functional pain assessments, including quantitative sensory testing (QST). We hypothesized that, when compared to NHW subjects, AA subjects would display 1) lower pain tolerance and higher ratings of heat‐, mechanical‐, and cold‐induced pain, 2) greater temporal summation of pain, 3) reduced pain inhibition, and 4) greater clinical pain and poorer function. In addition, we hypothesized that the findings from QST would significantly predict the severity of clinical pain within each race/ethnicity. Results AA subjects with knee OA displayed increased pain sensitivity, greater temporal summation, and reduced pain inhibition when compared to NHW subjects with knee OA. Moreover, AA subjects reported greater clinical pain and poorer function. Racial/ethnic differences in clinical pain became nonsignificant when the analyses were controlled for education and annual income, whereas differences in QST findings remained highly significant. Although the extent of pain inhibition predicted the severity of clinical pain in both groups, different QST measures were additionally predictive of clinical pain within each group. Conclusion The results of this study establish that there are racial/ethnic differences in experimental and clinical pain and function in older individuals with knee OA. Our findings indicating that different QST measures were associated with clinical pain within the 2 racial/ethnic groups, whereas reduced pain inhibition was important in all participants, warrant further study in order to elucidate the common and group‐specific pathophysiologic mechanisms contributing to clinical pain in OA.